1995
DOI: 10.1152/jappl.1995.78.3.968
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rM-CSF and rIL-6 therapy on immunosuppressed antiorthostatically suspended mice

Abstract: Antiorthostatically suspended mice had suppressed macrophage development in both unloaded and loaded bones, indicating a systemic effect. Bone marrow cells from those mice secreted less macrophage colony-stimulating factor (M-CSF) and interleukin-6 (IL-6) than did control mice. Because M-CSF and IL-6 are important to bone marrow macrophage maturation, we formulated the hypothesis that suppressed macrophage development occurred as a result of the depressed levels of either M-CSF or IL-6. To test the hypothesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…It has been shown that AHCC increases natural killer cell activity (25), , and nitric oxide production (28). Additional studies have shown that cytokine therapy reverses the immunosuppression seen in the hindlimb-unloading model (2,3). Although other factors such as stress hormones and other molecules released during the hindlimb-unloading period may affect the outcome of infection, it seems clear that, in our model of intraperitoneal inoculation of bacteria, innate immunity plays a critical role in resistance to infection.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that AHCC increases natural killer cell activity (25), , and nitric oxide production (28). Additional studies have shown that cytokine therapy reverses the immunosuppression seen in the hindlimb-unloading model (2,3). Although other factors such as stress hormones and other molecules released during the hindlimb-unloading period may affect the outcome of infection, it seems clear that, in our model of intraperitoneal inoculation of bacteria, innate immunity plays a critical role in resistance to infection.…”
Section: Discussionmentioning
confidence: 99%
“…The hindlimb unloading model has been adapted for use on mice to study the metabolic and immune responses of mice to antiorthostasis (3,4,8,40), as well as the musculoskeletal responses to unloading (36)(37)(38). With the increasing availability of transgenic and mutant strains of mice, the hindlimb unloading model is now being used to unravel molecular mechanisms that mediate responses to hindlimb unloading and antiorthostasis (10,24,28,44).…”
Section: Extension Of the System To Micementioning
confidence: 99%
“…There were also increases in the number of CD34 + cells in the bone marrow of mice assessed after the flight of STS-108 (Pecaut et al, 2003). Skeletal unloading, using antiorthostatic suspension, simulates some of the physiological changes associated with space flight (Chapes et al, 1993; Morey-Holton and Globus, 1998, 2002) also diminishes the number of macrophage progenitor cells in the bone marrow and affects hematopoiesis (Armstrong et al, 1993, 1994, 1995a; Dunn et al, 1983, 1985; Sonnenfeld et al, 1992). Therefore, there are important health issues that might arise from space flight impacts on hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%